Students’ Learning Interest Toward English for Nursing Dealing with Online Learning During the Covid-19 Pandemic Time - Iin Noviana; Pepin Nahariani; Shanti Rosmaharani; Rodiyah Rodiyah (Universitas Cokroaminoto Palopo, 2022)
Online learning is a learning process which is carried out by students and lecturers through the internet network. Students have the flexibility to study anytime and anywhere with online learning. The implementation of online learning greatly affects student interest in learning and causes anxiety experienced during the pandemic. This study aims to describe the learning interest of English subject of nursing students dealing with online learning during pandemic. The design of study used descriptive qualitative method with descriptive analysis of case study. The population of this study was 62 students and the sample used was 53 students who were taken using simple random sampling technique. The results showed that most of the respondents (69.8%) experienced a high interest in online learning. Student can provide learning interest, clear and easy to understand learning so that students who decreased interest in learning will be better and more diligent in their online learning efforts.